Lipidome changes, with a focus on phospholipids, due to feeding systems and processing in goat milk. (15th March 2021) - Argov-Argaman, Nurit; Glasser, Tzach; Muklada, Hussein; Hadaya, Oren; Mesilati-Stahy, Ronit; Raz, Chen; Landau, Serge Yan
Highlights: Lipidome components in goat – grazing or hay-fed in confinement was determined. Highest phospholipid contents was found in milk of grazing goat. Pasteurization and fermentation had only marginal effect on phospholipid content. Sensitivity to pasteurization of phospholipid composition differed between treatment groups. The composition of poly unsaturated fatty acids is significantly altered by processing. Abstract: We evaluated the effects of processing – pasteurization and yoghurt manufacturing – on some health-promoting lipidome components in milk from two feeding treatments – brushland grazing or hay-feeding in confinement – in dairy goats. The contents of fat and protein were higher, and of urea, lower, in grazing goats. Fatty acid composition – at the exception of saturated fatty acids – was affected by dietary management and milk processing. Phospholipid contents was lower in confined goats, with little effect for processing. The phospholipid-to-triglyceride ratio was decreased by pasteurization. Sensitivity to pasteurization of phospholipid composition differed between feeding treatments. The percentage of sphingomyelin increased following pasteurization, with no response for fermentation to yoghurt. These results can be exploited to modulate health-promoting fats in dairy products.